Risk factors for calcineurin inhibitor nephrotoxicity after renal transplantation: a systematic review and meta-analysis - Xia T; Zhu S; Wen Y; Gao S; Li M; Tao X; Zhang F; Chen W (Dove Medical Press, 2018)
Tianyi Xia, Sang Zhu, Yan Wen, Shouhong Gao, Mingming Li, Xia Tao, Feng Zhang, Wansheng Chen Department of Pharmacy, Changzheng Hospital, Second Military Medical University, Shanghai, People’s Republic of China Background: Nephrotoxicity of calcineurin inhibitors (CNIs) is the major concern for long-term allograft survival despite its predominant role in current immunosuppressive regime after renal transplantation. CNI nephrotoxicity is multifactorial with demographic, environmental, and pharmacogenetic flexibility, whereas studies indicating risk factors for CNI nephrotoxicity obtained incomplete or conflicting results.Methods: A systematic review and meta-analysis of risk factors for CNI nephrotoxicity was performed on all retrieved studies through a comprehensive research of network database. Data were analyzed by Review Manager 5.2 with heterogeneity assessed using the Cochrane Q and I2 tests. CNI nephrotoxicity was primarily indicated with protocol biopsy or index-based clinical diagnosis, and the secondary outcome was defined as delayed graft function.Results: Twelve observational studies containing a total of 2,849 cases were identified. Donor age (odds ratio [OR], 1.01; 95% CI, 1.01–1.03; p=0.02), recipient zero-time arteriosclerosis (OR, 1.44; 95% CI, 1.04–1.99; p=0.03), and CYP3A5*3/*3 genotype (OR, 2.80; 95% CI, 2.63–2.98; p=0.00) were confirmed as risk factors for CNI nephrotoxicity. Subgroup and sensitivity analysis claimed donor age as a significant contributor in Asian and Caucasian areas.Conclusion: Older donor age, recipient zero-time arteriosclerosis, and CYP3A5*3/*3 genotype might add up the risk for CNI nephrotoxicity, which could be interpreted into a robust biomarker system. Keywords: calcineurin inhibitor, transplantation, nephrotoxicity, risk factor, systematic review, meta-analysis